Pendidikan Penderita Gangguan Jiwa di Pesantren dalam Upaya Menjadikan Generasi Bangsa Berkarakter - Iwan Kuswandi (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2019)
This study talks about how is the solving of abnormal person by KyaiAbdurrahman and organizers as therapist in Pesantren Al-Bajigur TenonanManding Sumenep Madura? And what are the character education that is usedto educating to abnormal person in pesantren? The research is used qualitativeapproaching by kinds of case study. It is located in Pesantren Al-BajigurTenonan Manding Sumenep. The collected method of dates by observation toabnormal person in pesantren, and added by interview deepen to guardian andorganizers of pesantren who are therapists to student who has abnormal. Theanalysis dates is used based on model of Miles & Huberman. The result of thisresearch are about the method that is used by pesantren Al-Bajigur in handling ofabnormal person, namely: First, the family and patient invited to talkpersuasively. Second, patient gave thinking and took a bath. Third, patient wasgift ingredients meals. Fourth, patient is introduced to environment. And thefifth, patient is prayed as connection of horizontal to the God. And the charactereducation given are self-discipline character, environment care character,independent character, responsibility character, honest character and religiouscharacter.